Social and environmental conflits in the creation of Conservation Units: the Marinho das Ilhas dos Currais Case - Giraldi-Costa, Ana Clara; Murata, Afonso Takao (Revista Hipótese, 2015)
This article analyzes and discusses about the creation of the National Marine Park ”Ilha dos Currais” and the conflict generated with artisanal fishermen located in Matinhos city, of the Paraná state, Brazil. From Participant Observation can be said that the creation of the unit brought immediately, a material and symbolic character of conflict for the individuals involved, sometimes by the possible restriction on the access of customary fisheries resources in the region and sometimes the lack of participation of these actors in discuss of the National Marine Park “Ilhas dos Currais” creation process.